2016
DOI: 10.3389/fmicb.2016.01612
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Obesity Status and Dietary Intake of Monounsaturated and Polyunsaturated Oils on Human Gut Microbiome Profiles in the Canola Oil Multicenter Intervention Trial (COMIT)

Abstract: Long-term dietary fatty acid intake is believed to induce changes in the human gut microbiome which might be associated with human health or obesity status; however, considerable debate remains regarding the most favorable ratios of fatty acids to optimize these processes. The objective of this sub-study of a double-blinded randomized crossover clinical study, the canola oil multi-center intervention trial, was to investigate effects of five different novel oil blends fed for 30 days each on the intestinal mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(67 citation statements)
references
References 42 publications
4
57
0
Order By: Relevance
“…Via the fish oil supplement, we provided a dose of EPA and DHA (1.32 and 1.86 g/d, respectively) lower than that reported to have adverse events (5 g/d) [54] and lower than that showing changes in certain microbial genera (2 g/d EPA and 2 g/d DHA) [53]. However, it resulted in a much smaller difference in PUFA intake (1.84 percentage point) compared to the difference between monounsaturated fatty acid (MUFA) and PUFA interventions in the study by Pu et al [52] where PUFA intake differed by 7.2-9.4 percentage points (6.7-9.1 E% vs 16.3 E%). Third, the duration of the intervention is a factor important to consider since interesting results have been obtained following longer intervention with an ample washout period to demonstrate reversible effects after the PUFA intake [53].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Via the fish oil supplement, we provided a dose of EPA and DHA (1.32 and 1.86 g/d, respectively) lower than that reported to have adverse events (5 g/d) [54] and lower than that showing changes in certain microbial genera (2 g/d EPA and 2 g/d DHA) [53]. However, it resulted in a much smaller difference in PUFA intake (1.84 percentage point) compared to the difference between monounsaturated fatty acid (MUFA) and PUFA interventions in the study by Pu et al [52] where PUFA intake differed by 7.2-9.4 percentage points (6.7-9.1 E% vs 16.3 E%). Third, the duration of the intervention is a factor important to consider since interesting results have been obtained following longer intervention with an ample washout period to demonstrate reversible effects after the PUFA intake [53].…”
Section: Discussionmentioning
confidence: 60%
“…Although some extreme dietary changes can shift the gut microbiota composition within a few days, the response to some nutrients could be slower and depending on the concentration and overall dietary intake pattern. Pu et al observed effects after a 30-day intervention but the changes in fat quality were larger, total fat intake was constant and all consumed meals were provided during the intervention periods [52]. According to our longitudinal analysis of delta values (changes between the assessments of the four different sampling points) a longer dietary intervention might have been needed to detect PUFA effects on gut microbiota.…”
Section: Discussionmentioning
confidence: 62%
“…Our data are consistent with a recent randomized crossover clinical study in obese individuals where the effects of the gut microbiome were compared between supplementation with high oleic acid canola oil, and canola oil plus DHA. A principal analysis component carried by the authors revealed a strong enrichment of Lachnospiraceae in the canola plus DHA vs canola oil group, and more modest enrichments for Coprococcus and Ruminococcaceae 67 . Second, our study also lacked direct measurement of SCFAs in order to show a direct correlation between DHA serum levels and SCFAs in the gut.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of human gut microbiota contain: the Bacteroidetes phylum, the Firmicutes phylum [ 120 ], the Actinobacteria phylum, the Proteobacteria phylum, and the Verrucomicrobia phylum [ 121 ]. While the two former phyla contribute to 90% of the classes of the normal microbiome [ 6 ], the composition of microbiota in adults is stable and has a large inter-individual variation [ 121 ], which can be influenced by diet, BMI, age, intestinal diseases and medication, particularly antibiotics [ 65 , 121 , 122 ].…”
Section: Therapeutic Benefits Of Catechins To Ibdmentioning
confidence: 99%